2006
DOI: 10.3130/aijs.71.153_2
|View full text |Cite
|
Sign up to set email alerts
|

TESTS ON AXIAL LOAD CAPACITY OF SHEAR FAILING R/C COLUMNS CONSIDERING REINFORCING DETAILS : Relationship between axial loading test and lateral loading test

Abstract: Objectives of this study were 電o examine axial load carrying capacities of R 〆 C colurnns a 丘el shear failure , For this purpose static load血 g tests of R ! C colurms were conducted . Co 面 nement of hoop reinfo 【 cement to core concrete was one of the most important effects to be disoussed so different hoop

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In this section, the authors provide a summary of the equation for evaluating the lateral deflection angle at the axial capacity point for RC columns failing in shear, which was proposed by Kato et al in 2006, and shown here.…”
Section: Summary Of Evaluation Equation Proposed By Kato Et Al (2006)mentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, the authors provide a summary of the equation for evaluating the lateral deflection angle at the axial capacity point for RC columns failing in shear, which was proposed by Kato et al in 2006, and shown here.…”
Section: Summary Of Evaluation Equation Proposed By Kato Et Al (2006)mentioning
confidence: 99%
“…The axial load P fr,cal for calculation was empirically obtained using experimental data. Kato et al (2006), and the test data for the P and H series were reported by Kato et al (2004) in English. The test results include the lateral deflection and axial deformation at the axial capacity point, which were defined as maximum values observed during the loading tests.…”
Section: Summary Of Evaluation Equation Proposed By Kato Et Al (2006)mentioning
confidence: 99%
See 1 more Smart Citation